Managing future Gulf War Syndromes: international lessons and new models of care - Engel, Charles C (The Royal Society, 2006)
After the 1991 Gulf War, veterans of the conflict from the United States, United Kingdom, Canada, Australia and other nations described chronic idiopathic symptoms that became popularly known as ‘Gulf War Syndrome’. Nearly 15 years later, some 250 million dollars in United States medical research has failed to confirm a novel war-related syndrome and controversy over the existence and causes of idiopathic physical symptoms has persisted. Wartime exposures implicated as possible causes of subsequent symptoms include oil well fire smoke, infectious diseases, vaccines, chemical and biological warfare agents, depleted uranium munitions and post-traumatic stress disorder. Recent historical analyses have identified controversial idiopathic symptom syndromes associated with nearly every modern war, suggesting that war typically sets into motion interrelated physical, emotional and fiscal consequences for veterans and for society. We anticipate future controversial war syndromes and maintain that a population-based approach to care can mitigate their impact. This paper delineates essential features of the model, describes its public health and scientific underpinnings and details how several countries are trying to implement it. With troops returning from combat in Afghanistan, Iraq and elsewhere, the model is already getting put to the test.